Effective School Board Meetings. A Manual for Workshop Leaders. Keys to School Boardsmanship. A Program of Continuing Education for School Board Members Ray Jongeward. - Jongeward, Ray (Distributed by ERIC Clearinghouse, 1982)
The materials in this manual are designed to help workshop leaders prepare for and present a workshop for school board members on improving school board meeting practices for increased effectiveness. Based on successfully used procedures and recent research, the suggestions presented in the workshop are organized under seven headings: the agenda, the roles of the board and the district staff, leadership, decision-making, communication, time management, and the legal requirements of board meetings. The manual consists of six sections: an introduction; three sections on planning, presenting, and evaluating the workshop; a selection of resource materials; and a booklet for workshop participants. The discussion of planning contains information on the focus and scope of the workshop, familiarization with resource materials and equipment, workshop presentation techniques, and suitable grouping of participants. The presentation section includes sequential descriptions of workshop activities in each of the seven topic areas, leader focuses for each activity, and instructions for conducting the activities. The resource materials provided include papers on school board meetings, a discussion of recent research into board meeting effectiveness, and an article on resolving disagreements between board members. Masters from which transparencies for projection at the workshops can be reproduced are also included. (Author/PGD)